Research Regarding the Influence of Raw Material and Knitted Fabric Geometry on the Tensile Strength and Breaking Elongation. (2016) - Vlad, Dorin; Cioca, Lucian-Ionel
Abstract: The main purpose of this research paper is to increase the performance of knitting process during socks manufacturing by choosing the right knitted fabric geometry and raw material. On the other side, tests results show the wear resistance regarding mechanical properties like tensile strength and breaking elongation of knitted fabrics for socks. To obtain samples knitted fabric were used several types of some classic yarns, which already use to obtain socks organic also another type of yarns less used: cotton, organic cotton, bamboo viscose, soy + cotton, Tencel. From these yarns the following knitted fabric geometry were obtained: plated single jersey, plated ribb 4:2 and plated purl (rice grain). The tests were performed according with standard EN ISO 13934-2:2002 - Textiles -- Tensile properties of fabrics -- Part 2: Determination of maximum force using the Grab method. Graphs, results, conclusions and discussions was done.